Prosedur Pemeriksaan Radiografi Vertebrae Cervical pada Kasus Phlegmon di Instalasi Radiologi RSUD Kota Yogyakarta - Sefiana Nurul Hikmah; Amril Mukmin; Ayu Mahanani (Pusat riset dan Inovasi Nasional, 2025)
Phlegmon is a serious infection affecting the maxillofacial area. Cases of phlegmon cause more than 50% mortality before the development of antibiotics, and 90% are due to acute infection of molar teeth. Examination of cervical vertebrae can help the diagnosis by using AP Axial, Lateral, right posterior oblique (RPO)/left posterior oblique (LPO) projections of 15º-20º cephalad, and right anterior oblique (RAO)/left anterior oblique (LAO) 15º-20º caudad while in the Radiology Installation of Yogyakarta City Hospital, using AP Axial projection 15º cephalad, Lateral and oblique (RPO and LPO) with perpendicular beam direction without other modalities such as MRI and CT Scan. This study aims to further examine radiographic examination procedures and projections of RPO and LPO with perpendicular ray directions. This type of research is qualitative with a case study approach at the Radiology Installation of Yogyakarta City Hospital from September 2024 to May 2025. Data were collected by observation, documentation and interviews with 3 radiographers and 1 radiology specialist. Data analysis was done by data reduction, data presentation and conclusion drawing. The results showed 3-position photographs to evaluate the overall condition of the cervical vertebrae and surrounding tissues. RPO and LPO projections are not angled according to the applicable SOP and have no significant effect, because the main focus of phlegmon is soft tissue evaluation and is not related to the evaluation of nerve abnormalities in the intervertebral foramen. However, for phlegmon cases with serious severity, other modalities such as MRI, CT scan or ultrasound should be added in order to detect soft tissue and the cause of phlegmon for further action.